Hypothermia-induced accelerated idioventricular rhythm after cardiac surgery; a case report - Saeid Hosseini; Soheila Salari; Sepideh Banar; Yousef Rezaei; Atieh Tajik; Ali Zahedmehr; Zahra Emkanjoo (BMC Cardiovascular Disorders, 2023)
Abstract Background Accelerated idioventricular rhythm (AIVR) is a slow ventricular arrhythmia, commonly due to myocardial ischemia in coronary artery disease. It is a transitory rhythm that rarely causes hemodynamic instability or necessitates any specific therapy. Besides, the common predisposing factors for ventricular arrhythmias after open-heart surgery are hemodynamic instability, electrolyte imbalances, hypoxia, hypovolemia, myocardial ischemia and infarction, acute graft closure, reperfusion injury, and administration of inotropes and antiarrhythmic drugs. Here we report a case of AIVR after cardiac surgery, mostly due to hypothermia that to our knowledge, it is the first report. Case presentation We describe a 76-year-old man presenting with typical chest pain. Following routine investigations, the patient underwent coronary artery bypass grafting. Postoperatively, he was transferred to the intensive care unit with good hemodynamic status. However, about 3 h later, he developed rhythm disturbances, leading to hemodynamic instability without response to volume replacement or inotropic support. His rhythm was AIVR, although, at first glance, it resembled the left bundle branch block. Given his unstable hemodynamic status, he was emergently transferred to the operating room. Cardiopulmonary bypass (CPB) was resumed for hemodynamic support. After the patient was rewarmed to about 35 ºC, AIVR returned to normal. He was weaned from CPB successfully and with an uneventful hospital course. Conclusions Hypothermia is a potential cause of rhythm disturbance. Preventing the causes of arrhythmias, including hypothermia, is the best strategy.